Insights into BMAA neurotoxicity: evaluating Müller glial cell responses in retinal cultures - Viera, Solange (2024)
β-Methylamine-L-alanine (BMAA) is a non-proteinogenic cyanotoxin produced by various cyanobacteria, implicated in the etiology of neurodegenerative disorders such as Amyotrophic Lateral Sclerosis and Alzheimer›s disease, as well as certain retinal pathologies. Within the retina, BMAA exerts deleterious effects on neurons and Müller glial cells (MGCs), the primary glial cell type crucial for maintaining retinal homeostasis. Previous research has elucidated BMAA-induced neuronal degeneration while revealing no protective responses from MGCs, and BMAA-induced MGC metabolic alterations without affecting cell viability in pure retinal glial cultures.